The Acquisition of Survey Knowledge by Individuals With Down Syndrome - Himmelberger, Zachary M.; Merrill, Edward C.; Conners, Frances A.; Roskos, Beverly; Yang, Yingying; Robinson, Trent (Frontiers in Human Neuroscience, 2020)
Two experiments are reported that evaluated survey learning of youth with DS and typically developing children (TD) matched on Mental Age (MA). In Experiment 1, the experimenter navigated participants through a novel virtual environment along a circuitous path, beginning and ending at a target landmark (i.e., a door). Then, the participants were placed at a pre-specified location in the environment and instructed to navigate to the same door using the shortest possible path from their current location. They completed the task three times: once after being shown the environment one time, once after three exposures, and once after five exposures. Results indicated that the participants with DS exhibited significantly less skill at identifying the shortcut than did the TD participants. In Experiment 2, participants learned two overlapping routes through a simple environment. Following acquisition, they were tested on several measures of survey knowledge: finding a shortcut, identifying the direction of landmarks not currently visible from their location in the environment, and recognizing a bird’s-eye representation of the overall environment. The results of Experiment2 indicated that the participants with DS were at least as good as the TD participants on all of our measures of survey learning. Hence, we concluded that people with DS can acquire some survey knowledge when they learn a simple environment. However, the performance of both groups was relatively poor in Experiment 2, indicating a need to consider identifying the mechanisms underlying the poor performance on wayfinding of people with DS. Identifying the underlying mechanisms, is a logical first step in devising methods of enhancing environmental learning of people with DS.